Effect of rice husk addition on the physicochemical and hydrological properties on green roof substrates under subtropical climate conditions. (15th September 2021) - Liberalesso, Tiago; Tassi, Rutineia; Ceconi, Denise Ester; Allasia, Daniel G.; Arboit, Nathana Karina Swarowski
Abstract: Green roof substrates provide water, nutrients, and physical support to vegetation development, as well as being a key element in the hydrological performance of the system. In this regard, the use of aggregate components that improve physicochemical properties of the substrates optimises the ecosystem services provided by green roofs. This study demonstrates the effects of using rice husk as an aggregate material in engineered substrates for extensive green roofs. Sixteen different substrates compositions were tested with different proportions of natural (NRH) and carbonized (CRH) rice husk incorporated into a base mixture with fixed proportions of vermicompost, vermiculite, and construction waste. The study consists of two phases: i) laboratory analyses to assess the substrates' physicochemical properties, and ii) a pilot-scale field experiment to evaluate hydrological performance under real subtropical climate conditions and vegetation development using a monoculture planting of Sedum rupestre . The findings showed that CRH has the potential to improve some physicochemical properties, such as water holding capacity, bulk density, and porosity. Additionally, CRH substrates presented a slightly increased average retention rate (up to 7%) comparing to local topsoil. The average stormwater retention rate for all engineered substrates was 77.73%. Multiple linear regression models were satisfactorily fitted to observed data from the open field experiment allowing an estimation of potential substrates' retention rates. Moreover, vegetation development was positively affected by adding CRH comparing to the NRH. Carbonized rice husk presents as a useful material for improving green roof substrates properties and could be a sustainable alternative for local agriculture waste management. Graphical abstract: Image 1 Highlights: Adding carbonized rice husk (CRH) improves substrate' physicochemical properties. The average stormwater retention rate (RR) for engineered substrates was 77.73%. Substrates with higher content of natural rice husk (NRH) performs lower for RR. The regression models were fitted satisfactorily with moderate confidence level. CRH is a potential aggregate for the formulation of green roof substrates.